Data classification State institution National Antarctic Scientific Center - Globa, L. S.; Novogrudska, R. L.; Sidorenko, A. A.; Berezkina, A. (Ukrainian Antarctic Journal, 2016)
The paper presents an approach to creating a repository of Antarctic data. Antarctic data storage is a medium that allows you to store and access all primary ( «-raw» data) and secondary (research results) data. This repository is the core of the National Antarctic Data Center. The problem of classifying large amounts of data that must be displayed on the portal of the State institution National antarctic scientific center (SI NASC). The basic approach to the systematization of information. An analysis of the data contained within existing systems currently storage of SI NASC, and the domain of the proposed system in general classification SI NASC data that fully describes the entire array of provided information. A model of the National antarctic data center, describes the interface for accessing antarctic data storage and structure of the repository.